1995
DOI: 10.1016/0092-8674(95)90450-6
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulatory frameshifting in decoding mammalian ornithine decarboxylase antizyme

Abstract: Rat antizyme gene expression requires programmed, ribosomal frameshifting. A novel autoregulatory mechanism enables modulation of frameshifting according to the cellular concentration of polyamines. Antizyme binds to, and destabilizes, ornithine decarboxylase, a key enzyme in polyamine synthesis. Rapid degradation ensues, thus completing a regulatory circuit. In vitro experiments with a fusion construct using reticulocyte lysates demonstrate polyamine-dependent expression with a frameshift efficiency of 19% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
475
3
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(495 citation statements)
references
References 45 publications
13
475
3
4
Order By: Relevance
“…The expression of Az is tightly controlled at the post-transcriptional level by a þ 1 frameshift translation mechanism, which is regulated by the polyamine biosynthesis pathway. 21 Polyamine homeostasis in cells is modulated by the interplay of several anabolic and catabolic enzymes 22 and we have now shown that paox is specifically targeted by selected AP-1 factors that were activated upon exposure to chemotherapeutic drugs. PAOX is a FAD-dependent oxidase that preferentially retro-converts NASp to spermidine and N-acetylspermidine to putrescine.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The expression of Az is tightly controlled at the post-transcriptional level by a þ 1 frameshift translation mechanism, which is regulated by the polyamine biosynthesis pathway. 21 Polyamine homeostasis in cells is modulated by the interplay of several anabolic and catabolic enzymes 22 and we have now shown that paox is specifically targeted by selected AP-1 factors that were activated upon exposure to chemotherapeutic drugs. PAOX is a FAD-dependent oxidase that preferentially retro-converts NASp to spermidine and N-acetylspermidine to putrescine.…”
Section: Discussionmentioning
confidence: 92%
“…20 Az1 is a small inhibitory protein that binds to its target proteins and directs them to the proteasome for degradation. 21,22 Az1 transcript exists with two overlapping open reading frames, and translation of a fully functional Az1 protein requires a unique þ 1 ribosomal frameshift mechanism, which is dependent on the level of polyamines, a group of cationic compounds such as putrescine, spermidine and spermine present in the cells 21,22 ( Figure 1a, lower panel).…”
mentioning
confidence: 99%
“…Craigen and Caskey, 1986) and the rat ODCase antizyme gene (e.g. Matsufuji et al, 1995); and (iii) coding two proteins with a common N-terminal region and a different C-terminal region, e.g. the Escherichia coli dnaX gene (e.g.…”
Section: Biological Consequences Which Could Be Associated With the Pmentioning
confidence: 99%
“…If the spacing between the Shine-Dalgarno site and the frameshift trinucleotide is reduced to seven nucleotides then + 1 frameshift may occur (Larsen et al, 1994). Notes: the Shine-Dalgarno sites are observed six nucleotides upstream (−6) of the frameshift trinucleotides in the + 1 slipping process of prokaryotes (Weiss et al, 1988); a potential pseudoknot occurs five nucleotides downstream (+5) of the frameshift trinucleotide in the +1 slipping process of the ornithine decarboxylase antizyme gene of eukaryotes (Matsufuji et al, 1995). The window of X 0 could be involved in these different sequences of critical lengths (Larsen et al, 1994).…”
Section: Biological Consequences Which Could Be Associated With the Pmentioning
confidence: 99%
“…In fact, the total polyamine content of the Gy\Y cells was almost 3-fold that of normal X\Y cells ( Figure 3D), whereas the total polyamine content of Gy\Y mouse tissues was not even twice that of normal mouse tissues [27]. There are several possible methods by which spermidine can down-regulate ODC, for example by interfering with ODC mRNA translation [12] or by inducing ribosomal frameshifting of the antizyme mRNA [35], leading to the synthesis of antizyme, which promotes the degradation of ODC by the 26 S proteasome [14]. In a previous study we demonstrated that spermidine depletion causes decreased transcription of the antizyme gene [32].…”
Section: Figure 5 Induction Of Ssat By Bespd In Gy/y Cells (>) and Inmentioning
confidence: 99%